FORMULATION OF FILM SOAP CONTAINING 96% ETHANOL EXTRACT OF ARECA NUT (Areca catechu L.) AND ANTIMICROBIAL ACTIVITY TEST AGAINST Candida albicans - Linawaty Linawaty; Anisah Septiyani; Rahmi Hutabarat (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2025)
Vaginal infections causing leukorrhea (fluor albus) are a major reproductive health issue affecting many women, with the prevalence of Candida albicans fungal infections reaching 25–50%. Areca nut (Areca catechu L.) seeds are known to possess antimicrobial properties. This study aimed to develop a film soap formulation using 96% ethanol extract of areca nut seeds and to evaluate its antimicrobial effectiveness. The research was conducted experimentally in the laboratory, including sample collection and identification, preparation of 96% ethanol extract of areca nut seeds, and testing of antimicrobial activity against Candida albicans using the disk diffusion method. The results showed that the 96% ethanol extract of areca nut seeds contained several phytochemical compounds, including alkaloids, flavonoids, saponins, tannins, phenols, triterpenoids/steroids, and glycosides. Evaluation of the film soap included organoleptic tests, homogeneity, thickness measurement (0.13–0.4 mm), pH determination (4.67–5.00), and foaming ability (1.3–1.8 cm), all of which met the required standards. However, water content (36.45–43.40%) and weight uniformity (0.26–0.39 g) did not meet the requirements, indicating the need for further optimization. The antimicrobial activity test of the film soap showed average inhibition zone diameters at extract concentrations of 0%, 2.5%, 3%, and 3.5% were 10.4 mm, 15.3 mm, 17.4 mm, and 20.8 mm, respectively. These values indicated moderate to strong antimicrobial activity. The optimal concentration of antimicrobial film soap from areca nut extract was found at 3.5% (F3), as demonstrated by the inhibition zone diameter of 20.8 mm. This study concludes that the 96% ethanol extract of areca nut seeds can be formulated into film soap with antimicrobial activity comparable to that of the positive control.